PENGARUH TUMMY TIME EXERCISE TERHADAP KEMAMPUAN MOTORIK PADA BAYI : EVIDENCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Development is the acquisition of more sophisticated bodily structures and abilities in speech, language, communication, gross motor skills, fine motor skills, and independence. In Indonesia, 13–18% of children have developmental issues. Early stimulation can be used daily from birth to develop children's fine and gross motor skills, communication abilities, and emotional and mental development. Tummy time is one of the motor development training stimuli that can be used starting with neonates. Purpose: To determine whether tummy time exercise influences a baby's capacity to elevate his head. Method : Evidence base case report (EBCR) was done using multiple article literature searches, including PubMed and Science Direct. Result: At one month old, there was an increase in the motor lift of the head, lasting from 3.2333 seconds prior to stimulation to 9.003 seconds following tummy time. Conclusions: Tummy time exercises have been shown to improve a baby's capacity to lift their head when they are one month old.